Aripiprazole Long-Acting Injection During First Episode Schizophrenia—An Exploratory Analysis - Giordano, Gloria; Tomassini, Lorenzo; Cuomo, Ilaria; Amici, Emanuela; Perrini, Filippo; Callovini, Gemma; Carannante, Alfonso; Kotzalidis, Georgios D.; De Filippis, Sergio (Frontiers in Psychiatry, 2020)
Background. Long-acting injectable (LAI) aripiprazole was found to be efficacious in schizophrenia. In common clinical practice, the use of LAIs is often restricted to chronic patients with frequent relapses and poor compliance. Recently, some investigators advanced the idea of early LAI use also in young people with schizophrenia at their first psychotic episode (FEP). Objective. Our study aimed to assess the effect of LAI aripiprazole once monthly (AOM) in the treatment of FEPs in patients aged 18-26 years. Methods. We included 50 patients with DSM-5 schizophrenia as assessed with SCID, and used the Clinical Global Impression Scale-Severity of Illness (CGIs) and the Positive and Negative Syndrome Scale (PANSS) to assess symptom severity and the World Health Organization Quality of Life (WHOQOL), the Short Form Health Survey (SF-36) and the Personal and Social Performance Scale (PSP) to assess quality of life (QoL) and global health perception at baseline and 3, 6, 9 and 12 months after the first AOM injection. Results. AOM was associated with a progressive improvement of both positive (p<.001) and negative (p<.001) symptoms and in general psychopathology (p<.001) and decrease in global severity (p<.001). We also observed progressive improvement in QoL and social and personal functioning. Treatment adherence was 81.2% during the entire study. Our results support that AOM may improve psychotic symptoms, QoL and social functioning in young FEP patients. Further studies should compare AOM to its oral formulation in the treatment of young patients with schizophrenia at the outset of their illness.